The Effectiveness of a Self-Directed e-Learning Module on Trainee Knowledge and Confidence during Plastic Surgery Clinical Rotations - Pedram Akbari, MSc; Chantal R. Valiquette, MD; Shakira Brathwaite, MD; Greg Hawley, MD; Glykeria Martou, MD; J. Michael Hendry, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Exposure to plastic surgery is limited during medical school. This makes rotations for clinical clerks and off-service residents challenging. Available resources are often too detailed and overwhelming. Having an accessible, concise, and interactive plastic surgery e-learning module reviewing core plastic surgery topics could help prepare incoming trainees for their rotations. Methods:. An e-learning module was created using text, images, and in-house recorded video recordings. Two cohorts were recruited: control cohort (n = 9), who completed their plastic surgery rotation without use of the module, and an interventional cohort (n = 18), who completed the rotation with use of the module. A demographic survey, a 20-question multiple-choice knowledge test, and self-reported confidence score were completed by both cohorts at the end of their plastic surgery rotations. The intervention cohort also completed the knowledge test at the beginning of their rotation to establish baseline. Knowledge and confidence scores were compared using two-tailed, unpaired, nonparametric analyses (Mann-Whitney test). Results:. Learners from the intervention cohort reported a 95% module completion rate and found the resource “extremely helpful” (average Likert of 4.8/5). Learners indicated that they were very likely to recommend the resource to others (average Likert 4.9/5). The intervention cohort scored significantly higher on the knowledge test compared with the control cohort (P = 0.008), and on average reported higher confidence levels; however, this was not statistically significant (P = 0.057). Conclusion:. An accessible and concise module on core plastic surgery concepts enhances learner knowledge and confidence during plastic surgery clinical rotations.